Local Governance Strengthens Social Assistance's Impact on Sumatra's Poor Households' Welfare - Husna Purnama; Ahmad Dhea Pratama (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines the association between social assistance programs,, namely the Family Hope Program (PKH) and Non-Cash Food Assistance (BPNT,), and household consumption expenditure among the poor, while accounting for the role of regional financial management quality. Design/methodology/approach – The dependent variable is household consumption expenditure of the poor at the provincial aggregate level, measured in annual real terms. This study employs panel data from 10 provinces in Sumatra, Indonesia, for the period 2020–2025. Estimation is conducted using Ordinary Least Squares (OLS) and Moderated Regression Analysis (MRA) within a fixed-effects framework to assess interaction effects between social assistance variables and financial governance quality. Findings – The results show that the realization of PKH and BPNT beneficiaries is positively associated with household consumption expenditure among the poor. This association is stronger in provinces with higher-quality regional financial management. Budget realization is also positively associated with consumption expenditure. In addition, the Regional Financial Management Index (IPKD) strengthens the association between social assistance and household expenditure. These findings are associative in nature and based on aggregated provincial-level panel data. Originality/value – This study underscores the importance of financial governance quality in shaping the effectiveness of social assistance programs. It offers an integrated policy perspective by emphasizing the complementary roles of targeting accuracy, budget execution, and institutional capacity in improving economic conditions among poor households.